Study of serum magnesium levels in pre-diabetics and its correlation to body mass index - Koshy, Ajeesh; M., Roshan (International Journal of Research in Medical Sciences, 2021)
Background: Diabetes is a growing public health burden across the world, particularly in the developing countries. Homeostasis of the trace elements such as magnesium has been found to play an important role in the pathogenesis of diabetes and diabetic complications. Studies had found out an association between serum magnesium and incident diabetes; where diabetes may induce urinary magnesium loss. But in pre-diabetes, serum glucose levels are below the threshold for urinary magnesium wasting and hence unlikely to influence serum magnesium levels. This study was done to assess their serum magnesium levels and find its correlation. Methods: This cross sectional study was done among 120 pre-diabetic subjects. Pre-diabetes was diagnosed as per ADA guidelines and body mass index was calculated according to Asian guidelines of BMI. Serum magnesium levels were done for all of them and statistically analysed to correlate the serum magnesium with body mass. Results: The present study observed that 69 out of 120 pre-diabetics, 57.5% have low magnesium levels. This study showed that 57.5% of pre-diabetics is having normal body mass index, out of which more than half of them are having normal serum magnesium. But out of 12 obese pre-diabetics, 11 were having low serum magnesium 91.6%. (P value 0.026 which is statistically significant). Conclusions: This study observed that serum magnesium levels are low in Pre-diabetics. Significant hyomagnesemia has been seen in pre-diabetics with high BMI compared to those with normal BMI.